Comprehensive Review of Skill Development and Role Integration between Nurses and Nurse Assistants in Modern Healthcare - Alhadain , Ali Naji K; Alrizq , Nasser Ali S; Alyami , Ibrahim Awad A; Alyami, Fahad Awadh A; Almahamed , Rabia Hamad H; Gadyah , Safiah Ateeg H Al; Algadyah, Latifah Ateeg H; Al Yami , Rafaa Mohammed M; Alyami , Fatma Saleh S; Al Bahri, Mohsen Ojaym S; Al-Shammari , Asmahan Abdul Rahman A; Alanazi , Fawziah Khalid M; et al. (Journal of Ecohumanism, 2024)
Today, the versatile functions the nurses and nurse assistants perform are critically important to healthcare. This article focuses on skill acquisition, job overlapping, and the relationship between these two important healthcare positions. Thus, this review discussed the strengths and weaknesses of current literature, training approaches, and integration challenges to offer key recommendations on how healthcare organizations can enhance training integration. Implications for structured education, interprofessional communication, policy reforms, and teamwork are also discussed in relation to the findings.